Histopathological and Immunohistochemical Expression of Ki-67 and Alpha-Fetoprotein as Indicators in Various Gallbladder Diseases - Allami, Raghad A.; Mutlag, Ali M.; Al- Imami, Faris lutfi Nussrat (Journal of Neonatal Surgery, 2025)
Background: Gallbladder disease encompasses a spectrum of conditions affecting the gallbladder, including cholelithiasis (gallstones), cholecystitis (inflammation), gallbladder polyps, and gallbladder cancer. These disorders are influenced by multiple factors such as genetic predisposition, metabolic dysfunction, inflammatory pathways, and biliary stasis. Aim: This study aimed to evaluate the histopathological and immunohistochemical expression of Ki-67 and alpha-fetoprotein (AFP) in gallbladder tissue. Methods: This study was conducted at the College of Science, Wasit University, Iraq. Samples were collected from the Al Karama Teaching Hospital and Al Zahraa Hospital between October 2023 and July 2024. The study included 40 patients with cholecystitis (9 males and 31 females, aged 20–80 years) and 10 normal samples. The pathological classification categorized samples into acute cholecystitis, chronic cholecystitis, and hyperplasia. Immunohistochemical analysis was performed to assess in situ the Ki-67 and AFP expression. Results: Ki-67 expression increased progressively across the type disease recorded 1.2% in controls, 5.7% in acute cholecystitis, 8.93% in chronic cholecystitis, and 13.9% in hyperplasia, with a statistically significant association (p< 0.001). Overall, 72.5% of the samples tested positive for Ki-67 expression. In contrast, AFP expression remained low (1.0% in controls and acute cholecystitis, 2.05% in chronic cholecystitis, and 3.73% in hyperplasia) and showed no significant association with the disease type (p> 0.05). Only 15.0% of the samples tested positive for AFP. Conclusion: These findings indicate Ki-67 expression is significantly associated with gallbladder disease and serves as a strong marker of histopathologic lesion progression, while AFP expression remains minimal and statistically insignificant.